Value of Platelet Distribution Width and Mean Platelet Volume in Disease Activity Score of Rheumatoid Arthritis - Khaled SAA; NasrEldin E; Makarem YS; Mahmoud HFF (Dove Medical Press, 2020)
Safaa AA Khaled,1 Eman NasrEldin,2 Yasmine S Makarem,3 Hamdy FF Mahmoud4,5 1Department of Internal Medicine, Clinical Hematology Unit, Assiut University Hospital/Unit of Bone Marrow Transplantation, South Egypt Cancer Institute, Faculty of Medicine, Assiut University, Assiut, Egypt; 2Department of Clinical Pathology, Assiut University Hospital, Faculty of Medicine, Assiut University, Assiut, Egypt; 3Department of Rheumatology, Rehabilitation and Physical Medicine, Assiut University Hospital, Faculty of Medicine, Assiut University, Assiut, Egypt; 4Department of Statistics, Virginia Polytechnic Institute and State University, Blacksburg, VA 24061, USA; 5Department of Statistics, Mathematics and Insurance, Faculty of Commerce, Assiut University, Assiut, EgyptCorrespondence: Safaa AA KhaledDepartment of Internal Medicine, Clinical Hematology Unit, Assiut University Hospital/Unit of Bone Marrow Transplantation, South Egypt Cancer Institute, Faculty of Medicine, Assiut University, Assiut 71515, EgyptEmail safaakhaled2003@gmail.comBackground and Objective: Disease activity score 28 (DAS28) for rheumatoid arthritis (RA) is the commonly used DAS; it relies on clinical parameters that could be subjective. This work aimed to create a more accurate DAS for RA and assess its validity.Patients and Methods: The study included 98 RA patients and 53 matched controls; they were interviewed, clinically examined, their visual analogue scales (VAS) were reported, and then blood samples were withdrawn for erythrocyte sedimentation rate (ESR), complete blood count (CBC), and C-reactive protein (CRP). Platelet indices (PIs) were obtained from the CBC including Plt (platelet count), mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT). DAS28 was calculated for each patient using RheumaHelper mobile software. Minitab Statistical Package® and SPSS v20 software were used for data analysis.Results and Conclusions: Results revealed perfect matching between patients and controls as regarding age and gender. ESR, CRP and PDW were significantly higher in patients than controls; also positive correlations were detected among these variables. A new DAS for RA was developed; ESR, CRP, PDW and MPV were the components for this index. Further analyses showed that this new score was significantly higher in patients than controls and correlated with DAS28 of the patients. Furthermore the new score could identify RA patients from healthy subjects (cut off value < − 0.79) and stratified RA patients according to their disease activity into low, intermediate, high, or in remission. Conclusively, we developed a more precise, easily obtained new DAS for RA. This new DAS has both diagnostic/prognostic values in patients with RA.Keywords: rheumatoid arthritis, platelet indices, disease activity